Copolyester for low-shear melting applications

By using specific ratios of dicarboxylic acids, diols and polyols in the polymer, polyester with a stirring curve slope of -2 to -20 was prepared, and the polymer was solved in the low shear process solid to melt The problem of difficulty in body transformation improves processing efficiency and fluidity.

CN114729112BActive Publication Date: 2024-12-24EASTMAN CHEM CO
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202080081049.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-11-21
Filing Date
2020-11-19
Publication Date
2024-12-24
Estimated Expiration
2040-11-19

AI Technical Summary

Technical Problem

In the low shear process, existing polymers are difficult to convert from solid to flowable melt, resulting in low processing efficiency and low viscosity curve, which affects process cycle time and production efficiency.

Method used

Made by a low shear manufacturing process using polyester containing dicarboxylic acids, diols, polyols and optional branching agents, the agitation curve slope of -2 to -20, with a flowable melt from solid to flowable The sharp transition and steep viscosity curves with temperature change are suitable for rotary molding, powder smearing, powder coating and 3D printing processes.

Benefits of technology

Rapid melting and cooling of polymers in low shear processes is achieved, reducing cycle time, improving production efficiency, and allowing good flow under minimal heating conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114729112B_ABST
    Figure CN114729112B_ABST
Patent Text Reader

Abstract

The present invention relates to polyester compositions and their use in low shear manufacturing processes. More specifically, the present invention relates to polyester compositions having a sharp transition from solid to flowable melt, a viscosity curve that varies steeply with temperature, resulting in good flow with minimal heating above the melt temperature, and having minimal cooling requirements. The polyester has particular use in low shear polymer melt processes such as rotational molding, powder slush molding, powder coating, and 3D printing processes. The polyester is composed of at least one dicarboxylic acid, at least one dihydroxy alcohol, at least one polyol, and an optional multifunctional acid, alcohol, or anhydride branching agent. The polyester has a stirring curve slope of -2 to -20.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to polyester compositions. More specifically, the present invention relates to polyester compositions having a sharp transition from solid to flowable melt, a viscosity curve that varies steeply with temperature, resulting in good flow above the melt temperature with minimal heating, and minimal cooling requirements. This overall property allows for reduced cycle times and increased production efficiency in low shear polymer melt processes such as rotational molding, powder slush molding, powder coating, and 3D printing processes. Background Art

[0002] Some polymer melt processing operations require that the polymer be capable of processing at very low shear rates. These include rotational molding, powder slush molding, powder coating, and powder fusion processes for additive manufacturing. These technologies operate at very low to almost zero shear rates. Any shear or work applied to the material is based on the material's flow characteristics, such as viscosity and surface tension. Very little mechanical work is added to the material to aid in the mold filling or melting phase. Most polymer materials are not easily processed in low shear processes. Therefore, there is a need for polyesters that have a sharp transition from solid to flowable melt, with a viscosity curve that changes steeply with temperature, resulting in good flow above the melt temperature with minimal heating, and with minimal cooling requirements. These requirements are met in the polyesters of the present invention. Summary of the invention

[0003] According to one embodiment of the present invention, the present disclosure provides a method for manufacturing an article by a low shear manufacturing process, comprising melt puddling a solid polyester having a slope of -2 to -20 in a mold, dispersing the molten polyester onto a mold surface, solidifying the polyester to form a molded article, and removing the molded article from the mold.

[0004] In another embodiment of the present invention, the polyester comprises:

[0005] a. at least one dicarboxylic acid;

[0006] b. at least one dihydric alcohol;

[0007] c. at least one polyol; and

[0008] d. optional polyfunctional acid, alcohol or anhydride branching agent;

[0009] The slope of the stirring curve of the polyester is -2 to -20.

[0010] In another embodiment of the invention, the polyester comprises the following residues:

[0011] a. cyclohexanedicarboxylic acid (CHDA), and dimethylcyclohexane (DMCD);

[0012] b. Cyclohexanedimethanol (CHDM),

[0013] c. polytetramethylene ether glycol (PTMG), and

[0014] d. Trimellitic anhydride (TMA)

[0015] The slope of the stirring curve of the polyester is -2 to -8.

[0016] In yet another embodiment of the present invention, the polyester comprises:

[0017] a. Based on the total molar acid content of the polyester, 99 mol% to 100 mol% of a diacid selected from the group consisting of cyclohexanedicarboxylic acid (CHDA), dimethylcyclohexane (DMCD) and a combination thereof;

[0018] b. 75 mol% to 92 mol% of cyclohexanedimethanol and 8 mol% to 25 mol% of polytetramethylene ether glycol based on the total glycol content of the polyester;

[0019] c. Optionally, up to 1 mol % of a branching agent, based on the total molar acid content of the polyester, the branching agent being selected from the group consisting of glycerol, pentaerythritol, phenyl dianhydride, trimellitic anhydride and combinations thereof; and

[0020] The slope of the stirring curve of the polyester is -2 to -8.

[0021] In another embodiment, the present invention includes a method of coating a surface, comprising:

[0022] a. Spreading the powdered solid polyester onto the surface;

[0023] b. heating the powdered solid polyester to form a molten polyester coating; and

[0024] c. cooling the molten polyester coating to form a solid polyester coating;

[0025] The slope of the stirring curve of the polyester is -2 to -20.

[0026] In another embodiment, the present invention comprises an additive manufacturing method for producing a three-dimensional object, the method comprising the steps of:

[0027] a. applying a layer of polyester powder build material onto a target surface;

[0028] b. directing electromagnetic wave energy to the powder to form a sintered layer;

[0029] c. curing the sintered layer; and

[0030] d. Repeating steps (a) and (b) to form a three-dimensional object in a layer-by-layer manner;

[0031] wherein the polyester comprises the following residues:

[0032] i. Based on the total molar acid content of the polyester, 99 mol% to 100 mol% of the diacid, the diacid being selected from the group consisting of cyclohexanedicarboxylic acid, dimethylcyclohexanedicarboxylic acid and a combination thereof;

[0033] ii. 75 mol% to 92 mol% of 1,4-cyclohexanedimethanol and 8 mol% to 25 mol% of polytetramethylene ether glycol, based on the total glycol content of the polyester; and

[0034] iii. Optionally, up to 1 mol% of a branching agent selected from the group consisting of glycerol, pentaerythritol, phenyl dianhydride, trimellitic anhydride and combinations thereof, based on the total molar acid content of the polyester; and

[0035] The slope of the stirring curve of the polyester is -2 to -8.

[0036] In yet another embodiment, the present invention includes a polyester for use in a low shear polymer melt process comprising the residues of:

[0037] a. Based on the total molar acid content of the polyester, 99 mol% to 100 mol% of the diacid, the dibasic acid is selected from the group consisting of cyclohexanedicarboxylic acid, dimethylcyclohexanedicarboxylic acid and a combination thereof;

[0038] b. 75 mol% to 92 mol% of 1,4-cyclohexanedimethanol and 8 mol% to 25 mol% of polytetramethylene ether glycol, based on the total glycol content of the polyester; and

[0039] c. Optionally, up to 1 mol % of a branching agent, based on the total molar acid content of the polyester, the branching agent being selected from the group consisting of glycerol, pentaerythritol, phenyl dianhydride, trimellitic anhydride and combinations thereof; and

[0040] The slope of the stirring curve of the polyester is -2 to -8. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 is a graph of time (seconds) and temperature (degrees Celsius) versus average pixel intensity, depicting the polyester paddle curve. DETAILED DESCRIPTION

[0042] Unless otherwise stated, all numerals used in the specification and claims to represent the amount of components, properties such as molecular weight, reaction conditions, etc. should be understood to be modified by the term "about" in all cases. Unless otherwise stated, the numerical parameters set forth in the following specification and the appended claims are approximate values, which can vary according to the desired properties sought to be obtained by the present invention. At least, each numerical parameter should be interpreted according to the numerical value of the reported significant figures and by applying ordinary rounding techniques. In addition, the scope described in the present disclosure and claims is intended to specifically include the entire range, not just the endpoints. For example, the described 0-10 range is intended to disclose all integers between 0-10, such as 1, 2, 3, 4, etc., all decimals between 0-10, such as 1.5, 2.3, 4.57, 6.1113, etc., and endpoints 0 and 10.

[0043] Notwithstanding that the numerical ranges and parameters setting forth the broad scope of the invention are approximations, the numerical values ​​set forth in the specific examples are reported as precisely as possible. Any numerical value, however, inherently contains certain errors necessarily resulting from the standard deviation found in their respective testing measurements.

[0044] As used in the specification and the appended claims, the singular forms "a", "an", and "the" include plural references unless the context clearly indicates otherwise. For example, reference to "a polyester", "a dicarboxylic acid", "a residue" is synonymous with "at least one" or "one or more" polyesters, dicarboxylic acids or residues, and is thus intended to refer to a single or multiple polyesters, dicarboxylic acids or residues. In addition, reference to a composition containing or including "an" ingredient or "a" polyester includes other ingredients or other polyesters, respectively, in addition to the one mentioned. The terms "containing" or "including" are synonymous with the term "comprising", meaning that at least the named compounds, elements, particles, process steps, etc. are present in the composition or article or method, but does not exclude the presence of other compounds, catalysts, materials, particles, process steps, etc., even if other such compounds, materials, particles, process steps, etc. have the same function as the one named, unless explicitly excluded in the claims.

[0045] It should also be understood that reference to one or more process steps does not preclude the presence of additional process steps before or after the steps in the combination, or the presence of intervening process steps between those steps explicitly noted. In addition, letter designations of process steps or components, if any, are a convenient method for identifying discrete activities or components, and the recited letter designations may be arranged in any order unless otherwise indicated.

[0046] The term "polyester" as used herein is synonymous with the term "resin" and is intended to mean a polymer prepared by the polycondensation of one or more specific diacid components, a diol component, and an optional polyol component. The polyesters of the present invention are suitable for use in low shear polymer melt processes such as rotational molding, powder slush molding, powder coating, and 3D printing processes.

[0047] As used herein, the term "residue" with respect to the polymers of the present invention refers to any organic structure introduced into the polymer by a polycondensation or ring-opening reaction involving the corresponding monomers. It will also be understood by those of ordinary skill in the art that the associated residues in the various curable polyesters of the present invention may be derived from the parent monomer compound itself or any derivative of the parent compound. For example, the dicarboxylic acid residues mentioned in the polymers of the present invention may be derived from a dicarboxylic acid monomer or its related acyl halide, ester, salt, anhydride or mixture thereof. Therefore, as used herein, the term "dicarboxylic acid" is intended to include dicarboxylic acids and any derivatives of dicarboxylic acids, including their related acyl halides, esters, half esters, salts, half salts, anhydrides, mixed anhydrides or mixtures thereof, which can be used in a polycondensation process with a diol to prepare a curable aliphatic polyester.

[0048] The term "polyol" used in this application refers to polymeric diols, such as polytetramethylene ether glycol (PTMG), polyethylene glycol, polypropylene glycol, etc. In some embodiments of the present invention, the absolute molecular weight of the polyol is about 600 g / mol to about 5000 g / mol.

[0049] The term "branching agent" refers to an alcohol or acid molecule having three or more functional groups. Examples of alcohol branching agents include glycerol, trimethylolpropane, and pentaerythritol. Trimellitic anhydride is an example of an acid-based branching agent.

[0050] In normal extrusion and molding processes, polymer materials are heated and processed in a mechanical mixer that converts the material from a solid state to a molten state. In these processes, a lot of mechanical mixing and shear heating are used to assist the fusion process and flow of the material. Some examples of mechanically assisted melting processes include; single screw extrusion and twin screw extrusion. This can include film and sheet extrusion, profile extrusion, extrusion blow molding. Extruders are also used to process polymer materials for injection molding applications. In addition to single screw extruders and twin screw extruders, Ferrell mixers, Banbury mixers, Kokneader and other mechanical processes are also used to assist the melt fusion process. In these cases, mechanical energy is combined with heat to assist the fusion process from solid polymer to a flowable polymer melt.

[0051] Low shear manufacturing processes are those used for additive manufacturing such as rotational molding, powder slush molding, powder coating, and powder fusion processes. In such low shear manufacturing processes, the polymer material is transformed from a solid form to a molten form. The material then fuses together and, in some cases, flows to fill the mold, flows together to produce a stable part or a smooth or textured finished surface as required by the application. In these cases, there is minimal or no mechanical force added to the process to help the material melt and flow.

[0052] In the process proposed by the present invention, heat is essentially the form of energy applied to the polymer to transform the polymer from a solid material to a flowable polymer melt. This is also the primary variable in producing sufficient melt flow to allow the material to fill the mold in the case of rotational molding, or to fill highly textured surfaces such as those produced for automotive interior substrates, or to flow together to form a smooth surface in the case of powder coating, or to fuse and / or consolidate powdered materials in additive manufacturing.

[0053] Glass transition temperature (Tg), melting point (Tm), and dynamic melt viscosity are commonly used to describe and design melt processing of thermoplastics. Tg and Tm determine at what temperature a solid material can be made to flow. Dynamic melt viscosity determines how it will flow. When talking about dynamic melt viscosity, it is usually discussed as a shear rate dependent melt viscosity. Materials that exhibit a consistent melt viscosity as the shear rate changes are called Newtonian fluids. Materials that exhibit a decrease in viscosity as the shear rate increases are called non-Newtonian fluids and are shear thinning materials.

[0054] In the low shear applications targeted by the present invention, shear thinning is irrelevant. The levels of shear applied in rotational molding, powder slush molding, powder coating, and laser sintering are too low to observe any effect of the applied shear on changing the melt viscosity. The only important viscosity measurement for materials used in low shear processes is the effect of temperature on zero shear viscosity (or at least viscosity close to zero shear). At the low levels of shear present in applications where the polyesters of the present invention have utility, any effect of shear thinning will not be seen.

[0055] Ideal materials for low shear melt processing have the following characteristics:

[0056] It easily changes from a solid state to a molten state.

[0057] The temperature range from solid to flowable liquid is very narrow.

[0058] The polymer has a low melt viscosity to allow self-leveling and easy flow at process temperatures.

[0059] The melting temperature (Tm) is low enough to allow melt processing below the degradation temperature of the polymer.

[0060] The polymer readily transforms back into a solid upon cooling, resulting in a surface with high tear strength to facilitate removal of the molded part from the mold cavity surface.

[0061] The polyester melt characteristics will greatly affect the temperature window required for the process to run and the cycle time of the process. For example, in rotational molding, the mold is filled with powder or micro-granular material at a temperature below the glass transition temperature (Tg) or Tm (depending on whether the material is amorphous or crystalline). The mold is then rotated and placed into a heated chamber. The mold is heated until the material melts and flows to allow the mold to fill well. The mold is then removed from the heated chamber and continues to rotate as the mold cools until the part is strong enough to be safely removed from the mold.

[0062] The peak temperature needs to be high enough to completely melt the material and get it to a low enough viscosity to flow well and completely fill the mold. This principle also applies to other low shear processes. In the rotational molding industry, this transition is called "powder to puddle" and the cooling to a solid part is called the "return process." The faster the whole process is completed, the better. Materials with very sharp melting characteristics and steep temperature-viscosity curves are favorable to these processes and allow faster cycle times.

[0063] We have developed a family of materials that are particularly well suited for low shear processing applications. They display a sharp transition from solid to flowable melt (narrow temperature range from powder to paste), a steep viscosity vs. temperature curve that requires minimal heating above the paste temperature for good flow, and due to the first two factors, their cooling requirements are minimal. This overall performance allows for reduced cycle times and increased production efficiency in low shear polymer melt processes.

[0064] In some embodiments of the present invention, the dicarboxylic acid component of the present invention may include at least one dicarboxylic acid compound, a diester derivative thereof, an anhydride thereof, or a combination thereof. The dicarboxylic acid compound is capable of forming an ester bond with a diol or polyol compound.

[0065] In some embodiments of the present invention, the dicarboxylic acid component of the present invention may include alicyclic diacids, such as but not limited to hexahydrophthalic anhydride (HHPA), tetrahydrophthalic anhydride, tetrachlorophthalic anhydride, 5-norbornene-2,3-dicarboxylic anhydride, 5-norbornene-2,3-dicarboxylic acid, 2,3-norbornene dicarboxylic acid, 2,3-norbornene dicarboxylic acid anhydride, cyclohexane dicarboxylic acid (including 1,2-isomers; 1,3-isomers; and 1,4-isomers) (CHDA), dimethylcyclohexane (including 1,2-isomers; 1,3-isomers; and 1,4-isomers) (DMCD) and mixtures thereof.

[0066] In some embodiments of the present invention, the dicarboxylic acid component of the present invention may include an acyclic aliphatic diacid such as, but not limited to, adipic acid, maleic anhydride, maleic acid, fumaric acid, itaconic anhydride, itaconic acid, citraconic anhydride, citraconic acid, dodecanedioic acid, succinic acid, succinic anhydride, glutaric acid, sebacic acid, azelaic acid, and mixtures thereof.

[0067] In some embodiments of the present invention, the hydroxyl component of the polyester may include a diol component, such as but not limited to 2,2,4,4-tetraalkylcyclobutane-1,3-diol (e.g., 2,2,4,4-tetramethylcyclobutane-1,3-diol), 2,2-dimethyl-1,3-propanediol (neopentyl glycol), 1,2-cyclohexanedimethanol, 1,3-cyclohexanedimethanol, 1,4-cyclohexanedimethanol, 2,2,4-trimethyl-1,3-pentanediol, hydroxy Pivaloyl hydroxypivalate, 2-methyl-1,3-propanediol, 2-butyl-2-ethyl-1,3-propanediol, 2-ethyl-2-isobutyl-1,3-propanediol, 1,3-butanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 2,2,4,4-tetramethyl-1,6-hexanediol, 1,10-decanediol, 1,4-benzenedimethanol, ethylene glycol, propylene glycol, dipropylene glycol, diethylene glycol, triethylene glycol, and tetraethylene glycol.

[0068] In some embodiments of the present invention, the polyol includes, but is not limited to, polytetramethylene ether glycol (PTMG), polyethylene glycol, polypropylene glycol, and mixtures thereof.

[0069] In some embodiments of the present invention, optional branching agents may include polyfunctional acids, alcohols, anhydrides, and combinations thereof.

[0070] In some embodiments of the present invention, optional branching agents include, but are not limited to, 1,1,1-trimethylolpropane, 1,1,1-trimethylolethane, glycerol, pentaerythritol, erythritol, threitol, dipentaerythritol, sorbitol, neopentyl glycol, phenyl dianhydride, hexylene glycol, trimellitic anhydride (TMA), and combinations thereof.

[0071] In some embodiments of the present invention, the diacid component of the polyester includes cyclohexanedicarboxylic acid (CHDA) and dimethylcyclohexane (DMCD) and combinations thereof, the diethylene glycol component of the polyester includes cyclohexanedimethanol (CHDM), and the polyol includes polytetramethylene ether glycol (PTMG).

[0072] In some embodiments of the present invention, the diacid component of the polyester includes cyclohexanedicarboxylic acid (CHDA) and dimethylcyclohexane (DMCD) and combinations thereof, the diethylene glycol component of the polyester includes cyclohexanedimethanol (CHDM), the polyol includes polytetramethylene ether glycol (PTMG), and the branching agent includes trimellitic anhydride (TMA).

[0073] Examples

[0074] The invention has been described in detail with particular reference to preferred embodiments thereof, but it will be understood that variations and modifications can be effected within the spirit and scope of the invention.

[0075] In order to characterize the unique powder-to-cement characteristics of the polyesters of the present invention, a testing apparatus was used.

[0076] Materials in the examples (Ecdel TM 9966, commercially available from Eastman Chemical Company, Examples 1, 2, and 3) are all copolyesters based on a combination of cyclohexanedicarboxylic acid and cyclohexanedimethanol with polytetramethylene ether glycol (PTMG 1000) having a molecular weight of 1000. In the polyester synthesis process, CHDA and / or dimethylcyclohexanedicarboxylic acid (DMCD) may be used depending on the process. Up to about 1% trimellitic anhydride (TMA) may be used in the formula.

[0077]

[0078] Trimellitic Anhydride (TMA)

[0079]

[0080] 1,4-Cyclohexanedicarboxylic acid

[0081]

[0082] 1,4-Dimethylcyclohexanedicarboxylic acid

[0083]

[0084] 1,4-Cyclohexanedimethanol

[0085]

[0086] Polytetramethylene ether glycol (PTMG)

[0087] Experimental steps:

[0088] Polyester samples were prepared using polytetramethylene ether glycol (PTMG) commercially available from BASF and DMCD, TMA, and CHDM commercially available from Eastman Chemical Company. The following raw materials were charged to a 500 ml flask to produce 100 gram batches of polymer:

[0089] οDMCD 55.78g

[0090] οTMA 0.25g

[0091] οIrganox 1010 0.20 g (pentaerythritol tetrakis (3,5-di-tert-butyl-4-hydroxyhydrocinnamate, commercially available from BASF) was used as an oxidation stabilizer

[0092] οPTMG (HEIOOO) 25.1g

[0093] oCHDM (16) 37.58 g (including 2% excess)

[0094] οTi 70pmm catalyst

[0095] The following polymerization sequence is shown in Table 1:

[0096] Table 1

[0097] Time (minutes) Temperature(℃) Pressure (torr) Stirring speed (RPM) 0 220 760 0 2 220 760 25 1 220 760 158 60 220 760 158 25 270 760 158 1 270 0 158 10 270 0 158 1 270 0 60 5 270 0 60 1 270 0 16 1 270 100 0

[0098] The polyesters of the present invention are shown in Table 2:

[0099] Table 2

[0100] raw materials Ecdel9966 Example 1 Example 2 Example 3 CHDA or DMCD 99.5mol% 99.5mol% 99.5mol% 99.5mol% TMA 0.5mol% 0.5mol% 0.5mol% 0.5mol% CHDM 91.1mol% 85mol% 80mol% 75mol% PTMG 8.9mol% 15mol% 20mol% 25mol%

[0101] In order to quantify the powder-to-cement characteristics of the polyesters of the present invention, a test apparatus was set up as follows.

[0102] System Hardware:

[0103] The system is designed around a Nikon SMZ1000 stereo microscope, although others are available. Images were captured from the microscope's objective using a PointGrey Research Flea3 color camera (available from FLIR Integrated Imaging Solutions, Inc.). The camera was combined with the microscope using a 1″ CCD C-mount adapter from SPOTImaging Solutions. Two Zaber LSM 200A linear stages (available from Zaber Technologies, Inc.) were connected to form an X / Y stage system for rapid adjustment of sample position. A Linkam DSC 600 hot stage system (available from Linkam Scientific Instruments) was used to control heating and cooling cycles during experiments. In addition, a fiber optic halogen lamp system was used for sample illumination.

[0104] System Software:

[0105] The software integrating the digital camera and hot stage system was written using National Instruments (NI) Labview 2016. Using an ActiveX driver provided by Linkam, the manufacturer of the hot stage, serial commands can be sent and received to the hot stage device. This, combined with NI's Imaqdx driver, allows the creation of images with temperature and time information displayed in an overlay. Drivers for controlling the X and Y stages were also added to the software package to allow the user to precisely control the sample position. A simple user interface gives the user the ability to quickly run hot stage experiments with high reproducibility. The data is then written to the computer's hard drive in audio video interleave (AVI) format and can then be viewed using Windows' media player. Additional data processing routines were also written to provide a semi-quantitative measure of the time it took each sample to melt. This was accomplished using a custom image processing algorithm written using Labview. The basis of the algorithm involves quantifying the average pixel intensity of each image acquired from the sample. When powder samples melt, they typically undergo a visual change from white to transparent. Due to this effect, the average pixel intensity of the image is directly related to the physical state of the sample. This pixel intensity value can therefore be compared against time to generate a graphical representation of the melting process.

[0106] method:

[0107] Each selected material is melted in the same way using a programmable differential scanning calorimetry (DSC) hot stage. These melting processes are recorded using a microscope and digital camera system for sample comparison. Images from these video files can also be processed using image analysis techniques to generate a graphical representation of each melting process. Superimposing these melting curves on each other provides a semi-quantitative comparison of individual samples.

[0108] The puddle test measures the time required for a polyester to change from an opaque solid to a transparent melt at a temperature. The bottom x-axis is time and the top x-axis is temperature. The y-axis is a measure of pixel intensity. High pixel intensity is opaque (unmelted solid) and low pixel intensity is transparent (molten liquid). The results are shown in Figure 1 middle.

[0109] The slopes of the lines during the steepest transitions are given in Table 3:

[0110] Table 3

[0111] sample Slope = pixel intensity change / time change (s) Hytrel (DuPont) -1.0 TPU(Lubrizol) -0.6 Flexible PVC preparations -0.65 Ecdel9966(Eastman) -5.0 Example 1 -8.0 Example 2 -3.4 Example 3 -2.4

[0112] The steepness of the slope is related to the speed or temperature range required to transform from an opaque solid substance to a transparent melt. The slope of the line in the above figure can be used as a representative of the melting speed or melting range of the material. The melting point of a polymer is reported in a single number. However, polymer materials generally do not have a single melting temperature. Instead, polymers have a melting range. In a low shear process, high-speed melting or a narrow melting temperature range will lead to a faster processing cycle time. The inventor believes that the polyester within the scope of the present invention has a slope of -2 to -20, and has a sharp transition from a solid to a flowable melt, a viscosity curve that changes steeply with temperature, resulting in minimum heating above the melting temperature to obtain good flow, and has minimum cooling requirements. In some embodiments of the present invention, the polyester of the present invention may have a slope of -2 to -15. In other embodiments of the present invention, the polyester has a slope of -2 to -10, and in other embodiments of the present invention, the polyester has a slope of -2 to -8. These features allow for reducing cycle time and improving production efficiency in low shear polymer melting processes (such as rotational molding, powder slush molding, powder coating and 3D printing processes).

[0113] The invention has been described in detail with reference to the embodiments disclosed herein, but it will be understood that variations and modifications can be effected within the spirit and scope of the invention.

Claims

1. A method for manufacturing a molded article by a low shear manufacturing process, comprising: a. placing a solid polyester in a mold having a mold surface; b. heating the polyester until it becomes molten; c. dispersing the molten polyester on the mold surface; d. solidifying the molten polyester to form a solid molded article; and e. removing the molded product from the mold; wherein the polyester comprises: a. 99 mol% to 100 mol% cyclohexanedicarboxylic acid based on the total molar acid content of the polyester; b. 75 mol% to 85 mol% of 1,4-cyclohexanedimethanol and 15 mol% to 25 mol% of polytetramethylene ether glycol, based on the total glycol content of the polyester; and c. 0.5 mol% to 1 mol% of a branching agent based on the total molar acid content of the polyester, the branching agent being selected from the group consisting of glycerol, pentaerythritol, phenyl dianhydride, trimellitic anhydride and a combination thereof; and The polyester has a stir curve slope of -2 to -10, wherein the stir curve slope is determined by the steepest change in pixel intensity / time change, wherein the pixel intensity is measured by capturing an image of the polyester sample through the objective lens of a microscope using a digital camera when the sample is heated from 140°C at a rate of 10°C / 75 seconds using differential scanning calorimetry (DSC).

2. The method of claim 1, wherein the polyester comprises the following residues: a. Cyclohexanedicarboxylic acid; b. Cyclohexanedimethanol, c. Polytetramethylene ether glycol and d. trimellitic anhydride; The slope of the stirring curve of the polyester is -2 to -8.

3. The method according to claim 2, wherein the number average molecular weight of the polytetramethylene ether glycol is 600-5000.

4. The method of claim 1, wherein the polyester comprises: b. 80 mol% to 85 mol% of 1,4-cyclohexanedimethanol and 15 mol% to 20 mol% of polytetramethylene ether glycol, based on the total glycol content of the polyester; and The slope of the stirring curve of the polyester is -2 to -8.

5. A method for coating a surface, comprising: a. Spreading the powdered solid polyester onto the surface; b. heating the powdered solid polyester to form a molten polyester coating; and c. cooling the molten polyester coating to form a solid polyester coating; wherein the polyester comprises: a. 99 mol% -100 mol% cyclohexanedicarboxylic acid based on the total molar acid content of the polyester; b. 75 mol% to 85 mol% of 1,4-cyclohexanedimethanol and 15 mol% to 25 mol% of polytetramethylene ether glycol, based on the total glycol content of the polyester; and c. 0.5 mol% to 1 mol% of a branching agent based on the total molar acid content of the polyester, the branching agent being selected from the group consisting of glycerol, pentaerythritol, phenyl dianhydride, trimellitic anhydride and a combination thereof; and The polyester has a stir curve slope of -2 to -10, wherein the stir curve slope is determined by the steepest change in pixel intensity / time change, wherein the pixel intensity is measured by capturing an image of the polyester sample through the objective lens of a microscope using a digital camera when the sample is heated from 140°C at a rate of 10°C / 75 seconds using differential scanning calorimetry (DSC).

6. The method of claim 5, wherein the polyester comprises the following residues: a. Cyclohexanedicarboxylic acid; b. Cyclohexanedimethanol, c. Polytetramethylene ether glycol and d. trimellitic anhydride; The slope of the stirring curve of the polyester is -2 to -8.

7. The method according to claim 6, wherein the number average molecular weight of the polytetramethylene ether glycol is 600-5000.

8. Use of a polyester for a low shear polymer melt process, the polyester comprising the residues of: a. 99 mol% to 100 mol% cyclohexanedicarboxylic acid based on the total molar acid content of the polyester; b. 75 mol% to 85 mol% of 1,4-cyclohexanedimethanol and 15 mol% to 25 mol% of polytetramethylene ether glycol, based on the total glycol content of the polyester; and c. 0.5 mol% to 1 mol% of a branching agent based on the total molar acid content of the polyester, the branching agent being selected from the group consisting of glycerol, pentaerythritol, phenyl dianhydride, trimellitic anhydride and a combination thereof; and The polyester has a stir curve slope of -2 to -8, wherein the stir curve slope is determined by the steepest change in pixel intensity / time change, wherein the pixel intensity is measured by capturing an image of the polyester sample from the objective lens of a microscope using a digital camera when the sample is heated from 140°C at a rate of 10°C / 75 seconds using differential scanning calorimetry (DSC).

9. An additive manufacturing method for producing a three-dimensional object, the method comprising the following steps: a. applying a layer of polyester powder build material onto a target surface; b. directing electromagnetic wave energy to the powder to form a sintered layer; c. curing the sintered layer; and d. Repeating steps (a) and (b) to form a three-dimensional object in a layer-by-layer manner; wherein the polyester comprises the following residues: i. 99 mol% to 100 mol% cyclohexanedicarboxylic acid based on the total molar acid content of the polyester; ii. 75 mol% to 85 mol% of 1,4-cyclohexanedimethanol and 15 mol% to 25 mol% of polytetramethylene ether glycol, based on the total glycol content of the polyester; and iii. 0.5 mol% to 1 mol% of a branching agent based on the total molar acid content of the polyester, The branching agent is selected from the group consisting of glycerol, pentaerythritol, phenyl dianhydride, trimellitic anhydride and combinations thereof; and The polyester has a stir curve slope of -2 to -8, wherein the stir curve slope is determined by the steepest change in pixel intensity / time change, wherein the pixel intensity is measured by capturing an image of the polyester sample from the objective lens of a microscope using a digital camera when the sample is heated from 140°C at a rate of 10°C / 75 seconds using differential scanning calorimetry (DSC).